Odličnost drže - Hedžet Tóth, Cvetka (Slavistična revija, 2006)
The article discusses the dilemmas of theory in the era after the collapse of Bolshevist Socialism. Both philosopy and all of humanities are faced with the question how to interpret the notion of progress and history in the so-called post-historic era, which has returned the theory to the pre-Kantian level; as a consequence, tolerance is becoming the predominant category. The "call "back to the nature" critically confronts cyclism and linearism and the article points out the importance of preserving the utopia and the ability of utopian thinking, since the idea of the humanities itself originated in utopia. The modern era, which means the renaissance of ethic or,rather, the ethnicization of the world, cannot ignore the anthropological bases of the utopian and/or anticipating consciousness, which is always of this world, internal to the world, and such, it does not allow anything from the beyond, avbsolute substantiation; however, it preserves the idea of immoratality.
Keywords: ethics; etika; filozofija zgodovine; philosoph of history; solidarity; solidarnost; toleranca; tolerance; utopia; utopija